2010 IEEE International Symposium on Phased Array Systems and Technology 2010
DOI: 10.1109/array.2010.5613246
|View full text |Cite
|
Sign up to set email alerts
|

Innovative aperiodic arrays for SAR spaceborne applications

Abstract: In this paper an innovative procedure for the synthesis of linear non periodic phased arrays for SAR applications is presented. The main objective consists in minimizing the number of elements while optimizing the efficiency of the amplifiers. The procedure is implemented in three steps. Preliminary results are presented demonstrating that a reduction in the number of elements in the order of 20-30% with respect to existing conventional antennas may be achieved without sacrificing the performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Apparently, the RX power in one particular direction maximised if the TX and RX power patterns in this direction are identical, as revealed in (7). Technically, the identicalness of complex power value does not guarantee the identity of original complex number due to the phase ambiguity.…”
Section: Quasi-optimum Tx and Rx Pattern Decompositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the RX power in one particular direction maximised if the TX and RX power patterns in this direction are identical, as revealed in (7). Technically, the identicalness of complex power value does not guarantee the identity of original complex number due to the phase ambiguity.…”
Section: Quasi-optimum Tx and Rx Pattern Decompositionsmentioning
confidence: 99%
“…First is the large number of RF components that consume a lot of electrical energy, in both DC-RF conversion and heat dissipation. Sparse array with fewer active elements could be a possible solution and is widely studied [4][5][6][7][8]. The most critical drawback of the sparse array for space SAR application is that the antenna gain might degrade approximately proportional to the reduction of radiating element number.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiencies of large phased array antennas in the above four aspects have restricted the development and application of spaceborne SAR systems to a certain extent. Studies have shown that the above problems are expected to be improved when applying Uniform Amplitude/Equal Amplitude or Quantized Amplitude aperiodic array phased array antennas in spaceborne SAR systems [36][37][38][39]. The spacing between the elements of an Aperiodic Phased Array Antenna is usually not uniform [36,38,40,41].…”
Section: • Redundant System Performancementioning
confidence: 99%
“…In addition, the structural deformation caused by external loads will also change the electrical performance of the antenna during its service. For example, microstrip antennas are widely used in spaceborne synthetic aperture radar (SAR) antenna [9,10]. e antenna in orbit is in a very complex thermal environment [11].…”
Section: Introductionmentioning
confidence: 99%